Vacation in the Past - Effective Heritage Interpretation through Education - Réka Vasszi (EXARC, 2018)
Heritage sites are breathing memories from the past; however, visitors can hardly imagine or experience the ancient life on the spot. In fact, these visits are supposed to conjure up journeys back into the past and park managers should facilitate such experiences by the most effective means possible in order to help tourists gain an immersive ‘past experience’. Therefore, designing high quality and memorable visitor experiences is required in order to be profitable in tourism, and at the same time create awareness of heritage preservation. Accordingly, the paper presents the memorable visitor experience design and the corresponding teaching and learning theories for planning interpretative activities in museums and heritage sites. The results of the research demonstrate which interpretative tool is the most effective among 9-11 year-old students, in terms of a memorable experience and long-lasting learning.